Pengaruh Pemberian Pekerjaan Rumah Terhadap Prestasi Belajar Matematika Pada Peserta Didik Kelas IV Di Sekolah Dasar Subsidi Tarbiyatul Islam Sambas - Asmarita Asmarita; Eliyah Eliyah; Adnan Adnan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
This study uses a quantitative approach and the type of associative research. Data collection techniques using observation, questionnaires and documentation studies. The data analysis technique used is central tendency. Simple correlation and regression. The results showed that: 1) The provision of homework was classified as very good at 84.6%. Based on the data from the questionnaire results, it can be detailed giving homework with indicators: training students' discipline in learning, carrying out orders from the teacher, luring children to return to study at home. 2) Mathematics learning achievement of students at SDS Tarbiyatul Islam Sambas for the 2020-2021 academic year of 57.62% is in the 0.40-0 interval, quite good. Based on the data from the results of the questionnaire, it can be detailed with indicators of students' mathematics learning achievement, namely the UTS and UAS scores at SDS Tarbiyatul Islam Sambas for the 2020-2021 school year. 3) Giving homework does not have a significant effect on students' mathematics learning achievement at SDS Tarbiyatul Islam Sambas for the 2020-2021 school year. Based on the results of SPSS analysis, the sig value in the Anova table is 0.616, meaning Ho is accepted and Ha is rejected. It is interpreted that there is no significant effect between giving homework to learning achievement. The relationship between giving homework variable (X) to learning achievement (Y). shown by the model summary table with an R of: 0.116 or 11.6% in the